Implementasi Kaidah al-Ḍarar Yuzāl dalam Penyelesaian Masalah Ekonomi Digital Perspektif Maqāṣid al-Syarī‘ah - Abd. Rahman; Abdul Aziz Anwar; Imran Anwar Kuba; Achmad Musyahid (AHKAM, 2026)
The development of the Sharia digital economy in Indonesia provides ease of transactions, but it also gives rise to new risks, such as ambiguity in electronic contracts, exploitation of personal data, digital consumptive behavior, and weak consumer protection. Although previous studies have focused more on the formal legality of Sharia transactions, studies on the implementation of the principle of al-ḍarar yuzāl in preventing social and economic harm in the digital space remain limited. This study aims to analyze the relevance and implementation of the principle of al-ḍarar yuzāl in the Sharia digital economy from the perspective of maqāṣid al-syarī‘ah. This study used a qualitative approach with a literature study design through the analysis of scientific literature, regulations, fatwas, and documents related to Sharia fintech practices and the digital economy in Indonesia. Data were collected through documentation and searches of relevant academic sources and were then analyzed descriptively and interpretively. The results show that the implementation of the principle of al-ḍarar yuzāl in the Sharia digital economy has not been optimal because elements of gharar, weak contract transparency, digital algorithm manipulation, and low public digital literacy are still found. The findings also show a transformation in the meaning of harm in the digital space, which is not only manifested in financial losses but also includes the exploitation of personal data, psychological pressure, and technological dependence. From the perspective of maqāṣid al-syarī‘ah, the protection of wealth (ḥifẓ al-māl), intellect (ḥifẓ al-‘aql), and life (ḥifẓ al-nafs) serves as an important foundation for the development of the Sharia digital economy. The conclusion of this study emphasizes that the principle of al-ḍarar yuzāl is relevant as a normative basis for preventing harm in the Sharia digital economy. The implications of this study include the need to strengthen regulation, technological ethics, and Sharia digital literacy in order to realize a digital economic ecosystem that is fair, secure, and oriented toward public welfare.